Effect of a gamified education intervention with Kahoot on the levels of absenteeism from the degree in physiotherapy - Escriche-Escuder, Adrián; Martín-San Agustín, Rodrigo; Baño-Alcaraz, Aitor; Casaña Granell, José (My University, 2020)
Introduction: High levels of absenteeism have become one of the main problems in university education, due to the difficulty it causes in the implementation of basic active strategies such as self-guided learning. The gamified education tool Kahoot has become one of the most popular methods of gamification in the classroom environment. The aim of this study was to compare the levels of absenteeism obtained with the introduction of a gamified education methodology using Kahoot versus the traditional methodology of individual or group written tasks. Methodology: The Kahoot tool was used as a gamified education strategy on the Kinesitherapy subject of the Degree in Physiotherapy of the University of Valencia, with a total of 100 students enrolled. All the sessions included a presentation of contents. In addition, half of the ten sessions included the use of a gamification intervention, answering ten questions at the end of the session using Kahoot. Class attendance was assessed using the number of students who attended each class. The effectiveness of both options was evaluated by comparing means between the number of students attending the classes in which the Kahoot tool was used versus the number of students in the classes in which a traditional methodology was applied. Results: The analysis of the mean differences in class attendance revealed a statistically significant increase (p = .004) in the number of students present in the sessions with Kahoot (mean 70.8 (25.3)) with respect to the sessions without gamification (mean 52.6 (21.2)). In terms of percentage, there was a significant reduction in absenteeism in classes with Kahoot (mean 29.2%) compared to classes with a traditional approach (mean 47.4%). Conclusions: Based on the results in class attendance, Kahoot can be used as a gamified education tool to improve the participation and reducing the absenteeism in university studies of Physiotherapy.
Keywords: Educación; Tecnología educativa; Enseñanza superior - Efectos de las innovaciones tecnológicas; Fisioterapia - Estudio y enseñanza; Class atendance; Education; Innovation; Kahoot; Technology